Thermal and Physical Properties of Hybrid Composites Made from Used PET Bottles and Date Palm Fibers Filled with Unsaturated Polyester - Tahir Habila; Yazid Meftah; Samira Maou (ASEAN Journal of Chemical Engineering, 2023)
Recycling polyethylene terephthalate (r-PET) bottles is a sustainable solution for reducing the accumulation of r-PET in landfills. The primary goal of this study is to determine the viability of combining fibers derived from waste r-PET bottles (r-PET) and date palm fibers (DPF) to produce hybrid unsaturated polyester (UP)-based composites. Hand lay-up was used to make the UP/r-PET/DPF composites, which had 10%, 20%, and 30% r-PET and date palm fibers by weight, with equal weights of the two. Recycled r-PET bottles and date palm leaflets were cut into 5–10 mm lengths and incorporated into the UP matrix. The composites were characterized by their flexural, morphological, thermal, dynamical mechanical, and water absorption characteristics. The thermal behavior of the composites improved when r-PET and DPF were added at high temperatures. However, the composites' flexural strength and storage modulus decreased due to their non-uniform distribution, which made it hard for the fillers to adhere to the UP matrix. SEM micrographs of the composite's fracture surfaces showed that the amount of agglomeration eventually increased as the filler loading increased. Lastly, the composites showed significant resistance to water absorption with lower proportions of DPF and r-PET fibers.